2019
DOI: 10.1021/acsami.9b13904
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Phase Selective Growth of Two-Dimensional Perovskite/WS2 Heterostructures for Optoelectronic Applications

Abstract: Organic–inorganic hybrid perovskites have attracted increased interest owing to their exceptional optoelectronic properties and promising applications. Monolayers of transition metal dichalcogenides (TMDCs), such as tungsten disulfide (WS2), are also intriguing because of their unique optoelectronic properties and their atomically thin and flexible structures. Therefore, the combination of these different types of materials is very attractive in terms of fundamental science of interface interaction, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…Previously, we reported this unique selective growth behavior for MAPbI3 perovskite/WS2 heterostructures. 17) Our analyses revealed that the higher surface energy of WS2 compared to c-plane sapphire assists the growth of 2D perovskite layer 17) . As the selective growth takes place during the deposition of the PbI2 layer, we observe a similar growth behavior in FAPbI3.…”
Section: Characterizationsmentioning
confidence: 79%
See 4 more Smart Citations
“…Previously, we reported this unique selective growth behavior for MAPbI3 perovskite/WS2 heterostructures. 17) Our analyses revealed that the higher surface energy of WS2 compared to c-plane sapphire assists the growth of 2D perovskite layer 17) . As the selective growth takes place during the deposition of the PbI2 layer, we observe a similar growth behavior in FAPbI3.…”
Section: Characterizationsmentioning
confidence: 79%
“…In contrast, the PL from WS2 was strongly quenched. According to the band structure calculations, the heterostructure of FAPbI3 and WS2 possesses type-I band alignment 17,[24][25][26] . The type-I band alignment is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations